Lei Maria da Penha: uma nova forma de vida da mulher brasileira? - Prestes, Cleides Maria Silva [UNESP]; Nascimento, Edna Maria Fernandes dos Santos [UNESP] (My University, 2013)
This article proposes an analysis of the Law no. 11340, August 7th, 2006, known as “Maria da Penha” law. The study is based on the theoretical guidelines of French Semiotics, mainly on the earlier studies conducted by Algirdas Julien Greimas and the recent developments in Jacques Fontanille, Claude Zilberberg and Eric Landowski’s researches, concerning the forms of life. In this regard, we verify whether the aforesaid law constitutes a new way of life of the Brazilian woman.

Este artigo propõe uma análise da Lei n. 11340, de 7 de agosto de 2006, conhecida como Lei “Maria da Penha”. Para isso, valemo-nos de orientações teóricas da Semiótica francesa, principalmente dos estudos de Algirdas Julien Greimas e desdobramentos nas recentes pesquisas de Jacques Fontanille, Claude Zilberberg e Eric Landowski, no tocante a formas de vida. Nesse sentido, verificamos se a citada lei constitui uma nova forma de vida da mulher brasileira.
Law Maria da Penha: a new way of life of the Brazilian woman?
Keywords: law; Brazilian woman; Ways of life; Lei; Mulher brasileira; Formas de vida